Pasang Surut Politik dan Sejarah Isu Kebijakan Sawit di Riau - Khairul Anwar; Ishak Ishak; Isril Isril; Erman Erman (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2021)
This article aims to find the historical-political context of the ups and downs of oil palm policy issues in Riau by focusing on the early 2000-2010 reform period. The background is the political struggle of factors in the history of palm oil policy issues from colonial to early Indonesian reform, including in Riau. The argument is that the ups and downs of the political issue of palm oil occurred at the beginning of the reformation. How did the ups and down so political interaction between these actors take place in Riau? In answering the questions, Jeffry Frieden used theories and modern political economy analysis methods. Political ups and downs related to palm oil policy issues have occurred since Law No. 32/2009 and UU. No. 25/1999 were implemented. In the ORBA regime, politicians only made political demands in the DPRD and local bureaucracies. During 2000-2010, local actors who fought for the issue of palm oil had a wider spectrum. To a certain extent, many local actors were passive and then went viral. This period of political transition is expressed because several civil society activists, technocrats and the government have emerged. There are government actors who agree, reject and agree with the proposal. According to their position, the actors have strategies, tactics, and tips in forming a coalition. In the context of pluralistic local politics like this, the ups and downs of local politics on oil palm policy issues occur due to the interaction of local and national actors.